Game-Learning: a tangible RFID-based gamified system integrating pictophonics and reinforcement learning to accelerate early grapheme–phoneme acquisition - Guevara, Cesar; Bonilla-Jurado, Diego; Acosta-Vargas, Patricia (Frontiers in Education, 2025)
Reading proficiency is a cornerstone of children’s cognitive and emotional development, fostering both knowledge acquisition and intrinsic enjoyment. To transform early literacy into an engaging, playful experience, we introduce Game-Learning, a tangible educational prototype that merges pictophonic instruction, gamification, and operant reinforcement within an RFID-enabled toy. Game-Learning guides primary-age learners through multisensory grapheme–phoneme associations, pairing physical letter cards with interactive audiovisual feedback and reward mechanisms. We evaluated the platform in a 30-week quasi-experimental study involving 649 five-to seven-year-olds across 18 schools in Costa Rica (n = 311) and Ecuador (n = 338). Participants were randomly assigned to experimental (Game-Learning) or control (standard phonics instruction) groups. Pre-and post-tests assessed phonological awareness via a pictophonic reading protocol in Costa Rica and the Phonological Awareness Evaluation Test in Ecuador. During the intervention phase, experimental students used the Game-Learning system as part of their regular literacy lessons. Children in the experimental cohorts demonstrated significantly greater gains in both syllabic decoding (consonant–vowel combinations) and phonemic decoding (identification of single-letter sounds) compared to controls. By the post-test, over 85% of Game-Learning users reached age-appropriate mastery levels—more than double the improvement seen in the control groups—confirming the tool’s effectiveness as a reinforcement resource in both formal and informal learning environments.